Heights of tropopauses in some tropical cyclones over the Indian areas (MAUSAM, 1983)
Variation in the heights of tropopauses above tropical cyclonic storms in different stages of their evolution has been studied in the care of three different cyclonic storms formed in the Indian region. It was found that the tropopause may rise with a fall in temperature above a cyclonic or severe cyclonic storm when the cyclonic vortex extends sufficiently high into the lower stratosphere. It may sink with arise in temperature (i) over an easterly trough and (ii) may undulate in the peripheral anticyclone surrounding the core.